Determination of Polyphenols, Capsaicinoids, and Vitamin C in New Hybrids of Chili Peppers - Zsuzsa Nagy; Hussein Daood; Zsuzsanna Ambrózy; Lajos Helyes (Journal of Analytical Methods in Chemistry, 2015)
Six hybrids were subjected to chromatographic analyses by HPLC for the determination of phytochemicals such as capsaicinoid, polyphenol, and vitamin C. The dynamics of ripening of 4 of the hybrids were also characterised. Seven capsaicinoids could be separated and determined; the major compounds were nordihydrocapsaicin, capsaicin, and dihydrocapsaicin, while homocapsaicin and homodihydrocapsaicin derivatives were detected as minor constituents. Capsaicin content ranged between 95.5 ± 4.15 and 1610.2 ± 91.46 μg/g FW, and the highest value was found in Bandai (C. frutescens) at the green ripening stage. The major capsaicinoids had a decreasing tendency in Bandai and Chili 3735 hybrids, while no change was observed in Beibeihong and Lolo during ripening. Nine polyphenol compounds were detected including 8 flavonoids and a nonflavonoid compound in the pods of all hybrids. The major components were naringenin-diglucoside, catechin, and vanillic acid-derivative and luteolin-glucoside. Naringenin-diglucoside ranged from 93.5 ± 4.26 to 368.8 ± 30.77 μg/g FW. Except vanillic acid-derivative, dominant polyphenols increased or remained unchanged during ripening. As for vitamin C, its content tended to increase with the advance in ripening in all hybrids included in this study. The highest value of 3689.4 ± 39.50 μg/g FW was recorded in Fire Flame hybrid.